Mergers, acquisitions, and corporate restructurings - Gaughan, Patrick A. (Hoboken, New Jersey : Wiley, 2018)
'This book provides a comprehensive look at the field's growth and development, and places M & As in realistic context amidst changing trends, legislation, and global perspectives. All-inclusive coverage merges expert discussion with extensive graphs, research, and case studies to show how M & As can be used successfully, how each form works, and how they are governed by the laws of major countries. Strategies and motives are carefully analyzed alongside legalities each step of the way, and specific techniques are dissected to provide deep insight into real-world operations'--
Revised edition of the author's Mergers, acquisitions, and corporate restructurings, 2015.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 05, 2018).
Keywords: Consolidation and merger of corporations; Corporate reorganizations; BUSINESS & ECONOMICS -- Accounting -- Managerial; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Consolidation and merger of corporations; Corporate reorganizations; Electronic books